Changes in rumen capacity of dairy cows during the periparturient period - A.F. Park; J.M. DeFrain; Evan C. Titgemeyer; E.E. Ferdinand (Kansas Agricultural Experiment Station Research Reports, 2001)
Four-ruminally fistulated, multiparous, pregnant Holstein cows were studied to characterize ruminal adaptations during the transition from gestation to lactation. Cows were fed typical far-off and close-up diets, a late lactation diet containing wet corn gluten feed (20% DM), and an alfalfa hay, corn silage based early lactation diet. Ruminal measurements were obtained 72 (late lactation), 51 (far-off dry), 23 and 9 (close-up dry) days before expected parturition and 6, 20, and 34 days postpartum. Measurements included total fill, dry matter fill, fluid fill, and water-holding capacity of the rumen. Dry matter intake and milk production data were collected daily and body weight and body condition were determined weekly. Body weights and condition increased during the dry period, whereas intake as a percentage of body weight decreased. Ruminal water holding capacity, an indicator of rumen capacity, increased linearly from late lactation to 34 days postpartum. These data suggest rumen capacity is not the causative factor of intake depression in dairy cows during the final 3 wk of gestation.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Rumen capacity; Periparturient